TREATMENT OF DEPRESSION IN ELDERLY PATIENTS WITH CARDIOVASCULAR DISEASE - Ari Sumardika, I Wayan; Sri Diniari, Ni Ketut (E-Jurnal Medika Udayana; vol 2 no5(2013):e-jurnal medika udayana)
Cardiovascular disease and depression are two of the most common health problem that affect millions of people worldwide. Studies have shown that depression is a significant risk factor for newly diagnosed heart disease and that it increases morbidity and mortality in established heart disease. Many hypothesized and studied mechanisms have linked depression and heart disease, including serotonergic pathway and platelet dysfunction, inflammation, autonomic nervous system and hypothalamic-pituitary-adrenal axis imbalance, and psychosocial factors. The morbidity and mortality of cardiovascular disease is still associated with the treatment of depression. Understanding the impact and mechanisms behind the association of depression and heart disease may allow for the development of treatments aimed at reducing the bad outcomes that caused by these comorbid illnesses.
Keywords: depression, elderly, cardiovascular disease